ID, EGO, SUPEREGO TOKOH UTAMA DALAM FILM THE MESSAGE (AR RISALAH) 1976 - Putri Wulandari; R. Myrna Nur Sakinah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to determine the personality aspects contained in the fictional character in the movie "The Message (Ar Risalah) 1976" by Moustapha Akkad. The data obtained in the form of screenshots related to the id, ego, and superego of the characters Hamzah and Abu Sufyan as the main characters in the movie. This research uses descriptive qualitative method with the psycho-literary approach of Sigmund Freud. After doing the analysis, the author found the id aspect of Hamzah in the form of fear and a sense of self-defense when the Muslims were oppressed by the Quraysh infidels. The ego aspect is in the form of Hamzah's decisions in responding to the id. Meanwhile, the superego aspect found was in the form of Hamzah's guilt against the Prophet. The results of the analysis for the character of Abu Sufyan, namely the id aspect found in the form of the desires of Abu Sufyan which led to the death of the Messenger of Allah, the ego aspect found in the form of a decision between realizing the id or not, while the superego aspect is in the form of Abu Sufyan's guilt for his bad behavior towards the Messenger of Allah and the Muslims. Keywords: id, ego, superego, Hamzah, Abu Sufyan